Analysis of the Risk of Work Accidents for Field Officers PT PLN West Tanjung Jabung Regency, Jambi Province using the Hiradc Method - Anggraini, Widya; Sari, Rumita Ena; Aswin, Budi; Rini, Willia Novita Eka; Kusmawan, David (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to analyze the risk of work accidents among PT field officers. PLN West Tanjung Jabung Regency, Jambi Province using the HIRADC method. This type of research is based on the philosophy of post-positivism and is carried out to study the state of natural objects (not experiments). There were 7 research informants including 1 key informant, namely the K3L Implementing Officer of PT. PLN Kuala Tungkal, 2 main informants, namely the Head of PT. PLN Kuala Tungkal, and PT Performance Analysis. PLN Kuala Tungkal, 4 supporting informants, namely PT field employees. PLN Kuala Tungkal. Based on the results of the research, conclusions related to the risk analysis of work accidents among PT field officers. PLN West Tanjung Jabung Regency found 11 potential dangers after evaluating the risk ranking of accidents in the implementation of electricity production work in the operations division. There are 15 types of risk (37.5%) classified as medium risk, 22 types of risk (55%) classified as high risk, and 3 types of risk (7.5%) classified as very high risk (extreme risk). , and After analyzing the classification of work procedures, there are several work procedures, namely inappropriate work procedures, not being disciplined in using PPE when working.